Shifting paradigm: from Intellectual Quotient, Emotional Quotient, and Spiritual Quotient toward Ruhani Quotient in ruhiology perspectives - Achmad Ushuluddin; Abd Madjid; Siswanto Masruri; Mohammad Affan (IAIN Salatiga, 2021)
There are three theories of human intelligence, namely Intellectual Quotient (IQ), Emotional Quotient (EQ), and Spiritual Quotient (SQ). In its subsequent development, following the SQ era that considered the God Spot in the human brain as a source of intelligence, the concept of the Heart’s Code (HC) indicates that the source of intelligence lies in the heart, not the brain. The SQ model proposed by Zohar-Marshall and the HC model suggested by Pearsall only touched the biological and psychological realms, namely the material brain and the material heart. Both have yet to touch upon the transcendental level of divinity i.e. the spiritual brain and the spiritual heart. Using Thomas Kuhn’s scientific revolution approach, the current article intends to prove that the source of intelligence is not the brain but the ruh (the soul). When God has perfected the creation of man by blowing ruh in him, the sense of hearing subsequently radiates through the ears, sight through the eyes, smell through the nose, speech through the mouth, taste through the tongue, and intelligence through the brain. As a consequence, the brain is but a tool; it is not a source of intelligence. If IQ, EQ, and SQ are regarded as intelligence models originating from the human mind, which is certainly artificial in nature, then Ruhani Quotient (RQ) is an intelligence model originally created by God. Ruhani Quotient (RQ), which is based on ruh, has implications on new studies pertaining to ‘ruhiology.’